Stylistics of Attributes in the Poetry of Ratko Popović - Dejanović Simić, Milica J. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The poetry of Ratko Popović abounds in various types of attributes, which differ both in meaning and function. This paper employs an integrative stylistic method to describe their stylistic markedness. The analysis focuses on the attributes most dominant in Popović’s poetic language. The primary analytical framework is syntactic-stylistic, given that the unusual positioning of attributes is predominantly achieved through permutation of the conventional word order. In Popović’s poetry, attributes are realized in several ways: as congruent preposed attributes; non-congruent postposed attributes; anastrophic constructions; appositive and attributive forms; enveloped congruent attributes; chiastic and hyperbatonic structures; and figuratively employed attributes.
Keywords: congruent attributes; anastrophe; appositive attributes; attributives; hyphenated attributes